The Economics of Adaptation to Climate Change : Methodology Report - World Bank (Washington, DC, 2013)
The proposed methodology begins with a consistent downscaling of projected climatic changes from a multiplicity of General Circulation to local levels. Subsets of the suite of downscaled climatic factors are then to be used to estimate the vector of impacts on key economic sectors of each country, using sector-specific impact assessment models. Based on this information, alternative government adaptation projects will be specified and optimally chosen subject to a government budget constraint. Thereafter, direct impacts of climate change will serve as inputs into a macroeconomic framework to examine the indirect inter-sectoral impacts of climate change as well as adaption strategies. Finally, at each step the analysis will be complemented with perspectives and insights of people whose livelihoods are being or will be affected by changes in climate. Impacts of the climate change and the benefits of specific adaptation measures will be examined in the context of sub-populations defined by livelihood profiles. Local-level analysis of past and present autonomous adaptation measures for a range of groups stratified by sets of livelihood profiles will be conducted using participatory rural appraisal based primary fieldwork in addition to holding participatory workshops and consultations.